Split core technology allows efficient production of virus-like particles presenting a receptor-contacting epitope of human IgE - Baltabekova, A. Zh.; Shagyrova, Zh. S.; Voykov, M.; Ramanculov, E. M.; Shustov, A. V. (Nazarbayev University, 2014)
Immunoglobulin E (IgE) plays a central role in type I hypersensitivity including allergy and asthma. Novel treatment strategy envisages development of a therapeutic vaccine designed to elicit autologous blocking antibodies against the IgE. We sought to develop an IgE-epitope antigen that induces antibodies against a receptor-contacting epitope on human IgE molecule.
Keywords: immunoglobulin E; human IgE; immunodominant region; split core technology